2021
DOI: 10.1519/jsc.0000000000004062
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physiological Changes in Response to the Cumulative Demands of a Women's Division I Collegiate Soccer Season

Abstract: McFadden, BA, Walker, AJ, Bozzini, BN, Hofacker, M, Russell, M, and Arent, SM. Psychological and physiological changes in response to the cumulative demands of a women's division I collegiate soccer season. J Strength Cond Res 36(5): 1373–1382, 2022—This study sought to determine the effects of a women's collegiate soccer season on psychological markers, biomarkers, sleep, and performance. Athletes participated in maximal countermovement vertical jump height (CMJ) assessments and biomarker monitoring in conjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…Similarly, previous studies have assessed differences in RPE following each set rather than the overall session (11,30) which follows a similar pattern as sRPE in the current study. The Multicomponent Training Distress Scale score has not been assessed in previous research on this topic, but the current results show lower MTDS scores than previous data in team sports (34). Although there were no fluctuations in MTDS, DOMS exhibited different patterns of change between groups over the 6-week intervention.…”
Section: Discussioncontrasting
confidence: 89%
“…Similarly, previous studies have assessed differences in RPE following each set rather than the overall session (11,30) which follows a similar pattern as sRPE in the current study. The Multicomponent Training Distress Scale score has not been assessed in previous research on this topic, but the current results show lower MTDS scores than previous data in team sports (34). Although there were no fluctuations in MTDS, DOMS exhibited different patterns of change between groups over the 6-week intervention.…”
Section: Discussioncontrasting
confidence: 89%
“…It has been previously demonstrated that the accumulative stress of an entire season in NCAA Division I men’s [ 15 ] and women’s [ 16 ] soccer leads to significant hormonal perturbations, hematological changes and decrements in aerobic fitness and power, despite lower training loads as the season progressed, in relation to the higher workloads during the pre-season period. Further, post-season declines in soccer-specific fitness parameters appear to be related to the amount of match playing time completed by each player throughout the season [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While participants did not participate in testing on any given day if they were injured as defined in our exclusion criteria, anecdotally, the athletes complained of more "soreness," "tightness," etc, and sought athletic training services more frequently for treatment (ie, the athletic training clinic was visibly full of soccer players as the season progressed), without any diagnosed pathology. This observation is probably reflected in recent work that reported a continuous reduction in vigor in women's soccer players (as measured by the Multi-component Training Distress Scale) over the course of the season, 23,25 as well as an increase in depression at season's end. However, this remains somewhat conjectural since we did not administer a patient-reported outcome instrument to measure their impairments and health-related quality of life.…”
Section: Discussionmentioning
confidence: 89%
“…However, this is somewhat conjectural as other factors during the season, such as cumulative fatigue, injury, motivation, etc, may also contribute to a decline in performance. To our knowledge, no one has investigated changes in lower limb function tests during a competitive athletic season, but there is a small body of literature in soccer players reporting decreases in some performance tests during the season, 4,25 which were attributed to a net catabolic effect of the physiological load experienced during a competitive season. As such, we do not know the appropriate time of the season to collect baseline RTS test data to give us a metric of the athlete’s best ability to use as a benchmark should injury occur.…”
mentioning
confidence: 99%